Perawi Non-SunnnnÄ« dalam SahÄ«h Al-BukhÄrÄ« (Menemukan Nilai-nilai Toleransi dalam Ketatnya Kajian tentang Hadis Nabi) - Miski, Miski (UIN Sunan Kalijaga Yogyakarta, 2016)
Sahi>h al-Bukha>ri> is a masterpiece in hadithâ€™s field that known as the most authentic among others (beside Koran). There are some reasons for the extraordinary. One of them is the tight of the author (al-BukhÄrÄ«) on sorting out the sanads between him and the other narrators (ruwÄh) who are related to the Prophet. However, it canâ€™t be denied that apparently, some of the narrators follow the different sect (Shiah etc.) with the sect that al-BukhÄrÄ« do (SunnÄ«). Therefore, it can be understood that there are still some tolerance on the tight of his study for hadith. If we deepen, it can be concluded that this tolerance basically could be applied in the early context, that is in the plural life- the awareness of plurality, the field separation (secred and profane) and credibelity of each person.Keywords: Nilai-nilai Toleransi, Non-SunnÄ«, Sahi>h al-BukhÄrÄ«.